Potential use of Native Fruits Waste from Argentina as Nonconventional Sources of Cosmetic Ingredients - Orqueda, Maria Eugenia (2022)
Background: Collagenase, hyaluronidase, elastase, and tyrosinase enzymes are overexpressed and overactive in the skin aging process and hydrolyze the components of the dermal extracellular matrix (ECM) of the skin; these enzymes produce the clinical framework of aging, which includes skin dryness, hyperpigmentation, wrinkles, and inelasticity. Aims: The aim of this study was to explore the potential use of waste from two Argentine native fruits, namely Ziziphus mistol, and red and orange varieties of Solanum betaceum, as sources of bioactive compounds. Methods: Phenolic enriched extracts (PEE) from waste of Z. mistol and S. betaceum were obtained, and their total contents of phenolics and flavonoids were evaluated. The bioactive properties of the extracts were analyzed by measuring their antioxidant capacity and the inhibitory activity on collagenase, hyaluronidase, elastase, and tyrosinase enzymes. Results: The increased ability to inhibit the collagenase was demonstrated by the PEE of Z. mistol seeds and peel, while the enzyme elastase was mostly inhibited by extracts of S. betaceum skin. Z. mistol seed extract was the most active to inhibit hyaluronidase, reaching 96% inhibition at a concentration of 100 μg GAE/mL. The most active extracts to inhibit the tyrosinase enzyme were obtained from the peel of two varieties of chilto fruits, orange and red, and the mistol seed. Conclusions: The results obtained suggest that Z. mistol and S. betaceum waste may be considered as a source of bioactive phenolics. Here, Argentine native fruits waste is presented as a most promising alternative in cosmetic products, with future uses such as hydrogels, creams, or lotions.